KUALITAS FISIK DAN SENSORIS ROTI TAWAR BEBAS GLUTEN BEBAS KASEIN BERBAHAN DASAR TEPUNG KOMPOSIT PISANG GOROHO (Musa acuminate L) - Dwi Indah Surono; Ir. Erny J.N. Nurali, MS.; Ir. Judith S.C. Moningka, MS. (Universitas Sam Ratulangi, 2017)
The research was aimed to study the physical and sensory characteristics ofÂ bread made from composite flour of goroho flour, maize, and cassava starch.Â This study used a factorial randomized design with two factors, i.e : the proportion of goroho flour (with or without skin) and formulation of composite flour (G) i.e : 300 g goroho plaint flour : 120 g corn starch : 60 g cassava starch, 300 g goroho plaint flour : 90 g corn starch : 90 g cassava starch, 300 g goroho plaint flour : 60 g corn starch : 120 g cassava starch. The parameters analyzed were ratio of rising, porosity, texture, acceptance value of colour, aroma, flavor, and texture. The results showed that the type of goroho flour had highly significant effect on ratio of rising, porosity, and the hedonic. Interaction of the two factors had highly significant effect on texture. Formulation of goroho flour with skin, corn starch, cassava starch (300 g : 90 g : 90 g) produced bread with the best quality. Â Keyword : bread, composite flour, goroho flour